THE ESSENCE AND SIGNIFICANCE OF THE STRATEGY OF ENSURING THE FINANCIAL AND ECONOMIC SECURITY OF INDUSTRIAL ENTERPRISES - KUTSENKO, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article found out that the results of the financial and economic activity of enterprises are under the negative influence of the market environment. In addition, threats and risks can lead to a decrease in the level of financial stability, instability of activity, unprofitable functioning and bankruptcy of enterprises. Accordingly, it is expedient to timely identify and analyze factors of the external and internal environment, develop measures to neutralize their negative impact. All this is possible under the condition of a stable level of financial and economic security and the use of tools to ensure it, which will allow the enterprise to resume work, ensure the stability of functioning and determine the directions of development. Among such tools, the strategy of ensuring financial and economic security plays an important role. It was determined that the success of the enterprise depends on the level of economic security, which allows to protect it from the negative influence of the market environment. It is substantiated that one of the important components of economic security is financial security, which ensures the improvement of financial indicators of activity, the rational use of financial resources, and the growth of financial stability. A thorough analysis of the existing approaches of scientists to the definition of the concept of "economic security", "financial security", "financial and economic security", "strategy for ensuring financial and economic security" was carried out. The absence of an approach to the interpretation of the definition "strategy for ensuring the financial and economic security of the enterprise" was established, and an own vision of this concept was formed: a model of actions, tools for ensuring a stable level of economic and financial security by applying approaches, methods, functions, principles, software and resource support, taking into account interaction with the development strategy, management system and mechanism, which will guarantee the restoration, improvement, maintenance of the state of financial and economic activity, the level of financial and economic security, the avoidance of a crisis situation, the neutralization of the influence of factors, threats, risks in the short- and long-term period, provided that the appropriate type of strategy and will contribute to economic and financial development, the formation of economic balance. The difference between the proposed concept of "strategy for ensuring the financial and economic security of the enterprise" and already existing approaches is substantiated.
Keywords: economic security; financial security; financial and economic security; strategy; strategy for ensuring financial and economic security